Data set: autotrophic growth rates of Galdieria sulphuraria (Galdieri) Merola strains isolated from Italian acidic sites - Petraretti, Mariagioia; Mormile, Nicolina; Del Mondo, Angelo (BORNH Bulletin of Regional Natural History, 2021)
Intraspecific variability (strain differences) in Galdieria sulphuraria growth rate was assessed in laboratory growth tests carried out under autotrophic conditions. Here a complete data set of experiments is presented . 23 G. sulphuraria strains presently maintained in the ACUF collection of cyanobacteria and microalgae were selected on the basis of the geochemical characteristic of their sampling sites, scattered over Center-South Italy and Sicily. The results have shown that the growth rate values obtained ranged from 0.437 to 0.070, and fail to highlight any relationship between growth rates and geochemical features of sampling sites . Our results also raise the question if the observed differences in growth rates of G. sulphuraria strains were independent of the long-term preservation in the ACUF facilities.The marked differences in growth rate observed in this set of experiments could drive a more effective selection of G. sulphuraria strains amenable for biotechnological applications.